Face recognition for identity enabling system (FRIES) - Hacla, Marlon B. (2001)
Face Recognition for Identity Enabling System (FRIES) is a software designed to recognize faces in real time. The project is divided into modules - face segmentation and face recognition. The LVQ algorithm is used to generate the codebook vectors used for skin segmentation. The captured images, after being segmented, are then converted to gray scale format as inputs to the second module. The second module used the backpropagation algorithm for the recognition part. This part is responsible for uniquely classifying one face from another. After several trainings, the software is able to properly recognize a face with an accuracy rate at around 97%.